Billi: Wearable, AI assisted bill identifier for the blind - Aban, Steven Claude N.; Baldonado, Greian Kif A.; Muro, Cyron Paul T.; Rodriguez, Ralph Emmanuel D.; Tecson, Christian James G. and Tuazon, Morthon Jhayzie. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Computer Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2